2021
DOI: 10.1371/journal.pone.0250351
|View full text |Cite
|
Sign up to set email alerts
|

Effects of “fresh mechanically deboned meat” inclusion on nutritional value, palatability, shelf-life microbiological risk and digestibility in dry dog food

Abstract: Fresh mechanically deboned meat (MDM) is usually claimed as high-quality ingredient on dry pet food recipes and this aspect may positively influence consumer choice. It is important to determine the scientifically sustainability of this claim and to assess the microbiological safety of MDM inclusion in dry pet food. Objectives were: 1) to evaluate the effect of inclusion of MDM in dry dog food on fatty acid profile and in vivo and in vitro digestibility, proposing a new system (DaisyII Incubator) to measure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Knight & Satchell (2021) also stated that high levels of crude protein in dog diets interfere with palatability, digestibility and faeces quality. In addition to the high crude protein content, some authors mention that high fat content also contributes to palatability results, as a preference for moist or semi-moist foods (Meineri et al, 2021;Samant et al, 2021). Souza et al (2022b) in their study tested different levels of carcass flour inclusion with Nile tilapia head residues.…”
Section: Resultsmentioning
confidence: 99%
“…Knight & Satchell (2021) also stated that high levels of crude protein in dog diets interfere with palatability, digestibility and faeces quality. In addition to the high crude protein content, some authors mention that high fat content also contributes to palatability results, as a preference for moist or semi-moist foods (Meineri et al, 2021;Samant et al, 2021). Souza et al (2022b) in their study tested different levels of carcass flour inclusion with Nile tilapia head residues.…”
Section: Resultsmentioning
confidence: 99%
“…Total fecal samples were collected during the last 4 d of the experimental period ( Meineri et al, 2021 ). All fecal samples were weighed, scored, and stored at −20 °C until analyzed to determine macronutrient ATTD using the ­formula:…”
Section: Methodsmentioning
confidence: 99%
“…From the pet owners' perspective, fresh meat benefits from a more healthy, nutritive, and palatable image than meals and byproducts [107,108], but it does not reflect cat and dog food preferences. Koppel et al [109] compared the impact of the inclusion of mechanically deboned chicken, i.e., fresh poultry, against the inclusion of chicken byproduct meal on the sensory characteristics and volatile profile of kibbles.…”
Section: Protein Sourcesmentioning
confidence: 99%
“…Over the 30 descriptors evaluated by human panelists on appearance, taste and aftertaste, flavor, texture, and mouthfeel, only bitterness, fishiness, and cohesiveness of mass were affected by the inclusion of fresh meat over meat meal. Recently, some studies compared fresh meat or chicken to meat meals and meat or chicken byproduct meals [107,108]. In both studies, two-bowl tests showed a significant preference for byproduct meals over fresh materials, with an intake ratio and first choice of approximately 70% for the processed ingredients.…”
Section: Protein Sourcesmentioning
confidence: 99%
See 1 more Smart Citation